Persistence with Anticoagulation for Atrial Fibrillation: Report from the GLORIA-AF Phase III 1-Year Follow-up - Kozieł, Monika (J Clin Med, 2020)
Background: We aimed to assess the extent to which drug persistence is better with non-vitamin K antagonist oral anticoagulants (NOACs) than vitamin K antagonists (VKAs) in atrial fibrillation (AF) patients and to estimate the difference in therapy persistence depending on NOAC dosing regimen (once daily (QD) vs. twice daily (BID)). Methods: Consecutive patients were followed for 1 year in phase III of the GLORIA-AF registry. Drug persistence was defined as the use of OAC without any discontinuation in >30 days or switching to alternative therapy. Results: Among 21,109 eligible patients in phase III, 17,266 patients who were prescribed OAC at baseline and those who took ≥1 OAC dose were included. The 1-year proportion of patients receiving NOAC and VKA who persisted on treatment was 80% and 75%, respectively. The 1-year persistence with NOACs BID and NOACs QD was 81% and 80%, respectively. Female gender, hypertension, older age, alcohol use, permanent, asymptomatic, and minimally symptomatic AF were associated with better OAC persistence. Region, medication usage predisposing to bleeding, being a current smoker, treatment reimbursement, and proton pump inhibitors were associated with lower OAC persistence. Conclusions: Drug persistence was higher with NOACs (1-year persistence was 80%) than with VKAs (75%). There was little difference in 1-year persistence between NOAC dosing regimens.